1975
DOI: 10.1002/j.1537-2197.1975.tb12333.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Stratification Temperature and Germination Temperature on Germination and the Induction of Secondary Dormancy in Common Ragweed Seeds

Abstract: Stratification of common ragweed (Ambrosia artemisiifolia) seeds at 4 C was most successful for breaking dormancy, whereas -5 C was least effective and 10 C was intermediate. Germination in the light exceeded that in the dark at all stratification and germination temperatures. The optimum temperatures for germination in the light were 10/20, 15/25, and 20/30. Maximum germination in the dark occurred at 20/30 C for seeds stratified at 4 and 10 C but the optimum temperatures for seeds stratified at -5 C were 10/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
1

Year Published

1977
1977
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 19 publications
1
36
0
1
Order By: Relevance
“…the number of plants in the region). This is because Ambrosia seeds require moist chilling (stratification) before they can germinate (Pickett and Baskin 1973;Willemsen 1975;Baskin 1977, 1980). Ambrosia plants that emerge earlier have been shown to grow larger, and Ambrosia pollen production is directly correlated with biomass (Rogers et al 2006;Fumanal et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…the number of plants in the region). This is because Ambrosia seeds require moist chilling (stratification) before they can germinate (Pickett and Baskin 1973;Willemsen 1975;Baskin 1977, 1980). Ambrosia plants that emerge earlier have been shown to grow larger, and Ambrosia pollen production is directly correlated with biomass (Rogers et al 2006;Fumanal et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Other Galium species exhibit strong seed dormancy. Since stratified seeds germinated well at moderate (22°C) temperature, G. cracoviense might be expected to establish dense populations even when the seeds are dispersed in fields abandoned in early or late summer (Willemsen, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…The primary dormancy of A. artemisiifolia is mainly due to the presence of inhibitors such as phenolic compounds (similar to chlorogenic acid) and abscissic acid [11], while in A. trifida seed dormancy can be attributed to an inhibitory mechanism within the embryo (embryo dormancy) or constraints on the embryo imposed by the embryo-covering structures (coat-imposed dormancy) [12,13]. For both species prolonged periods of cold stratification (several weeks at 4-5°C), simulating what occurs under field conditions in the winter season, remove primary seed dormancy promoting germination [14][15][16]. Particular conditions occurring during stratification (ie alternating temperature regimes in darkness conditions) can induce in A. artemisiifolia a secondary dormancy [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…A. trifida non-dormant seeds germinate under a wide range of temperatures (from 8 to 41°C) with an optimum between 20 and 24°C [19]. Emergence of common ragweed seedlings occurs mainly from soil surface and drastically decreases by increasing planting depth [15]. Abul-Fatih and Bazzaz [19] reported that giant ragweed emerged from seeds buried over a range of depths from 0.5 to 16 cm, but maximum emergence occurred when seeds were buried at 1 to 4 cm.…”
Section: Introductionmentioning
confidence: 99%